2015
DOI: 10.1039/c5ta07180a
|View full text |Cite
|
Sign up to set email alerts
|

Facile interfacial charge transfer across hole doped cobalt-based MOFs/TiO2 nano-hybrids making MOFs light harvesting active layers in solar cells

Abstract: a Efficient charge separations and their mobility is a key challenge in metal-organic-frameworks (MOFs) based devices. In the present study, thin films of cobalt-based metal organic frameworks (MOFs) are synthesized using layer-by-layer technique, and their electrical/optoelectronic properties are studied. The as-prepared MOF films show electrically insulating behavior, which after hole doping demonstrate p-type conducting material. The measured HOMO-LUMO energy states of the MOF films are found to be well mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 46 publications
(60 reference statements)
4
33
0
Order By: Relevance
“…Hall effect measurements on films of CoBDC and CoNDC grown on TiO 2 and doped with I 2 showed similar mobility values of 21.2 and 87.6 cm 2 V –1 s –1 , respectively. 253 …”
Section: Guest-promoted Transportmentioning
confidence: 99%
“…Hall effect measurements on films of CoBDC and CoNDC grown on TiO 2 and doped with I 2 showed similar mobility values of 21.2 and 87.6 cm 2 V –1 s –1 , respectively. 253 …”
Section: Guest-promoted Transportmentioning
confidence: 99%
“…67 Afterwards, the I2-doping strategy has been successfully reproduced with a considerable number of insulating MOFs. The appearance of electrical conductivity was due to either donor-acceptor interactions between I2 and ligand π electrons, [68][69][70][71][72] the oxidation of the network [73][74][75] or conduction through polyiodide ions. [76][77][78] Although in some of these conduction mechanisms were not clearly elucidated.…”
Section: Infiltration Of Non-conductive Guestsmentioning
confidence: 99%
“…Marking the advances of the MOF field in recent years, at first, optically and redox-silent MOF thin films were employed in DSSCs as simple dye-loading materials to enhance the dye-loading capacity and prevent dye aggregation. , Although this strategy helped improve V OC by impeding charge recombination, the insulating MOFs also hindered long-range charge movement and injection processes, diminishing the photocurrent density and overall efficiency of devices compared to those without MOFs . The thin films of several traditional MOFs based on colorless aromatic ligands also displayed photovoltaic response upon iodine infiltration (PCE up to 1.2%), but their inabilities to absorb visible–NIR light and generate photocurrents without iodine doping left the origin of photovoltaic behavior unclear and highlighted the need for intrinsically light-harvesting frameworks based on more powerful chromophores, such as porphyrin, perylene, and Ru­(bpy) 3 2+ dyes. Although the energy-transfer capability and catalytic activities of such light-harvesting MOFs have been widely explored, their photovoltaic properties remained largely overlooked until lately possibly because the latter also required properly oriented MOF films attached to electrode surfaces to support requisite charge separation, movement, and injection processes. Recently, Wöll, , Allendorf, and others have demonstrated that porphyrin-based MOFs could produce modest photocurrents under visible light (PCE: 0.0026–0.45%), whereas Morris et al demonstrated that Ru­(bpy) 3 2+ -based MOFs experienced slightly greater PCE than corresponding molecular Ru­(bpy) 3 2+ complexes (∼0.12 vs 0.08%).…”
Section: Introductionmentioning
confidence: 99%